Valsartan Induced Melanoma?! First Description in Medical Literature! - Tchernev, Georgi (Open Access Maced J Med Sci, 2018)
BACKGROUND: Drug-induced carcinogenesis is a matter of huge popularity and the subject of in-depth research over the last few years. According to the literature, dopamine agonists and acetylsalicylic acid fall into the list of drugs likely to potentiate the development of cutaneous melanoma. However, according to recent data, widely used angiotensin receptor blockers (ARBs) for the treatment of arterial hypertension, also carry a risk of malignancy development. The content of probable carcinogens, such as NDMA or NDEA in the drug valsartan (ARBs), causes the product to be withdrawn from the market. Recent experimental data suggest that another angiotensin receptor blocker-losartan also stimulates cell adhesion and melanoma cell invasion. CASE REPORT: We present a 70-year-old patient who has been on systemic therapy with a combined drug of amlodipine and valsartan since 2008 and only valsartan from 2015. Three years after the first intake of valsartan (2011), the patient developed a pigment lesion on the right arm. Approximately 2.5 years after doubling the dose of valsartan, the patient observed a progression in the size of the lesion, which was the cause of the dermatological examination and hospitalisation for surgical removal. The melanocytic lesion was removed by radical excision and a surgical field of 0.5 cm in all directions, followed by histological verification, which found the presence of cutaneous melanoma with a tumour thickness of 3 mm. A re-excision was planned with an additional surgical field of 1.5 cm in all directions combined with parallel removal of a draining lymph node. CONCLUSION: The case is indicative of two things: 1) the possible triggering of melanoma within the systemic treatment with valsartan; and 2) the necessity for optimization of melanoma surgery within the one-step melanoma surgery, which in this case would result in a single surgical excision of the primary lesion, with an operational security field of 2 cm in all directions, along with the removal of a draining lymph node.